Increasing students' Understanding in Medical Surgical Nursing courses about Factors That Can Affect Early Mobilization of Mothers Post Sectio Caesarea at the Rumah Sakit Ibu dan Anak Banda Aceh - Yeni Rimadeni (Jurnal Serambi Ilmu, 2022)
The purpose of this study was to determine and improve the ability ofstudents directly about the factors that influence the early mobilization ofpostoperative cesarean mothers. This study uses a descriptive correlationalresearch method with the approach used is cross sectional. The number ofsamples of 30 respondents was taken using the Non Probability samplingmethod with accidental sampling technique. The results showed that therewas no relationship between pain and early mobilization with a P-value(0.784), there was no relationship between anxiety levels and earlymobilization with a P-value (0.445), there was a relationship betweenknowledge and early mobilization with a P-value (0.008). and there is arelationship between motivation and early mobilization with a P-value(0.001). Factors that influence early mobilization of postoperative sectiocaesarea mothers at the Rumah Sakit Ibu dan Anak Banda Aceh areinfluenced by several factors such as knowledge and motivation. From theresults of this study, it is hoped that it can be useful for postoperative sectiocaesarea mothers, for hospitals to be able to improve the evaluation of earlymobilization in postoperative sectio caesarea mothers from pain factors,anxiety levels, knowledge and motivation